Building Religious Moderation through Strengthening Mawaddah-Based Social Cohesion in Cigugur District, Kuningan Regency - Wardah, Deda Aenul (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2024)
Efforts to strengthen religious moderation are faced with great challenges along with the strengthening of ideologies that preach intolerance, radicalism, and terrorism. These ideas indirectly erode the principle of moderation, causing a myriad of problems in society. Not to mention, the existence of identity politics further exacerbates divisions and differences in society, which in turn triggers attitudes of intolerance and radicalism, as happened in the Batu Satangtung case in Cigugur sub-district, Kuningan district. These problems imply a contradiction with the values of the Quran that always uphold tolerance and harmony between religious communities. This paper offers a Quranic solution through the actualization of the concept of mawaddah by strengthening social cohesion. This study uses a qualitative approach with a case study research type. Quranic verses are discussed thematically using descriptive-analytic techniques. This study found that the concept of mawaddah can be actualized by strengthening social cohesion so that, in turn, religious moderation will be realized. The form of social cohesion based on Al-Quran values can be manifested in various activities, such as: 1) economic activities; 2) arts and cultural activities; 3) agricultural activities.